2020
DOI: 10.1177/0146167220948712
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity Moderates the Link Between Environmental Beliefs and Pro-Environmental Support: The Role of Belief in a Controlling God

Abstract: The current research examines differences in what motivates environmentally sustainable behavior between more and less religious people in the United States. We found that religiosity moderates the extent to which environmental beliefs predict pro-environmental support. Specifically, environmental beliefs predicted pro-environmental support less strongly among more religious people than less religious people (Studies 1 and 2). Using a correlational (Study 2) and an experimental (Study 3) design, we further fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…This deemphasis on self-expression in religion influences what primarily drives action. Our research has found that how strongly environmental beliefs predict proenvironmental action depends on religiosity (Eom, Saad, & Kim, 2019). Using international data from 32 countries ( International Social Survey Programme , 2010; ISSP Research Group, 2019), we found that religiosity, both at the individual and national levels, moderated the association between personal awareness of environmental issues and proenvironmental action.…”
Section: Religionmentioning
confidence: 97%
“…This deemphasis on self-expression in religion influences what primarily drives action. Our research has found that how strongly environmental beliefs predict proenvironmental action depends on religiosity (Eom, Saad, & Kim, 2019). Using international data from 32 countries ( International Social Survey Programme , 2010; ISSP Research Group, 2019), we found that religiosity, both at the individual and national levels, moderated the association between personal awareness of environmental issues and proenvironmental action.…”
Section: Religionmentioning
confidence: 97%
“…The study of this diversity in human responses to climate change has become an increasingly important project in psychology, and in the social, behavioral, and biological sciences more generally (Hornsey et al, 2016; Pearson & Schuldt, 2018). Heeding this call, a number of research programs have examined how sociocultural characteristics such as culture (Eom et al, 2016; Tam & Chan, 2017), socioeconomic status (SES; Ballew et al, 2020; Eom et al, 2018), religion (Eom et al, 2020; Schuldt et al, 2017), and race (Schuldt & Pearson, 2016) affect climate change beliefs and sustainability behaviors (see Eom et al, 2019 for review).…”
mentioning
confidence: 99%
“…This is the explanation of the third point in table 1. Religion is a source of external control [21], control that comes from God. Religion guarantees sustainable behavior through the concept of an omniscient divinity, the concept of karma or reward and sin.…”
Section: Resultsmentioning
confidence: 99%